Factors Affecting the Occurrence of Out-of-Hospital Sudden Cardiac Arrest - Izabella Uchmanowicz; Wiesław Bartkiewicz; Jarosław Sowizdraniuk; Joanna Rosińczuk (Emergency Medicine International)
Objective. This paper aims to discover the risk factors for sudden cardiac arrest (out-of-hospital sudden cardiac arrest (OHSCA)) which significantly affect the decision about prioritizing emergency interventions before dispatching medical emergency teams, risk of deterioration of the patient’s condition at the scene, and emergency procedures. Methods. A retrospective study taking into account the international classification of diseases ICD-10 based on an analysis of medical records of Emergency Medical Service in Wroclaw (Poland). Results. The main risk factor of OHSCA is coexistence of external cause leading to illness or death (ICD Group V-10) as well as the occurrence of diseases from the group of endocrine disorders (group E), in particular diabetes. The increase in the risk of OHSCA incidence is affected by nervous system diseases (group G), especially epilepsy of various etiologies, respiratory diseases (group J), mainly COPD, and bronchial asthma or mental and behavioral disorders (group F), with particular emphasis on the drugs issue. The procedure for receiving calls for Emergency Notification Centre does not take into account clinical risk factors for sudden cardiac arrest (SCA). Conclusion. Having knowledge of OHSCA risk factors can increase the efficiency of rescue operations from rapid assessment and provision of appropriate medical team, through effective performance of medical emergency treatment and prevention of SCA or finally reducing the costs.